The The Centrality of the Actor-Network of the Manpower Bill in Tempo's Weekly Magazine Reporting - Radita Gora (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The drafting of the Job Creation Bill (RUU) invites public controversy to the occurrence of a community movement rejecting the Job Creation Bill and also the omnibus law. This has invited Tempo magazine to report on the draft regulation by placing statements of certain actors in the news as well as Tempo's tendency to involve actors in its communication network. So here it is indicated that there is a problem of ambiguity in the involvement of political actors in the news. Through the use of media sovereignty theory to examine the media in utilizing their freedom of authority, as well as analysis of communication networks to identify the presence of the central actor in Tempo's reporting. Here it is found that the network density is low, the relationship between actors and actors needs to go through several steps so that the network distribution is very wide. In addition, Tempo has an imbalance in placing political actors in Tempo's reporting, so political actors are not fully explained in terms of their relationships, including the network relations between these political actors.